The Effect of Inflation, Exchange Rate, BI Rate and Dow Jones Index to Indonesia Composite Index in Indonesia Stock Exchange on the Year 2013-2018 - Hasanudin (GoAcademica Research & Publishing, 2021)
The purpose of this study is to demonstrate the influence of inflation, currency exchange rates, SBI interest rates, and the Dow Jones index on the Jakarta Composite Index on the Indonesian Stock Exchange from 2013 to 2018. Methods of quantitative research utilizing Structural Equation Modeling (SEM) analytic techniques in conjunction with the use of SmartPLS 3. The findings of this study indicate that inflation has a substantial negative influence on the CSPI. This indicates that as inflation increases, the JCI decreases. The exchange rate has a substantial negative effect on the JCI. This demonstrates that the exchange rate variable has a direct effect on the direction of the high exchange rate, lowering the JCI in the process. The SBI interest rate has no effect on the JCI and is rather detrimental to it. This indicates that when the number of SBI interest rates increases, the CSPI remains same. The Dow Jones index has a sizable positive correlation with the CSPI. This indicates that the Dow Jones index's rise has an effect on the JCI. By a factor of 0.982, the Dow Jones Index has the greatest effect on work motivation, followed by inflation, exchange rates, and SBI interest rates on the IHSG on the 2013-2018 Stock Exchange.